2019
DOI: 10.3390/s19112596
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Spectroscopy and Cobalt Electrochemistry Data for Estimating Phosphate Concentration in Hydroponic Solution

Abstract: Phosphate is a key element affecting plant growth. Therefore, the accurate determination of phosphate concentration in hydroponic nutrient solutions is essential for providing a balanced set of nutrients to plants within a suitable range. This study aimed to develop a data fusion approach for determining phosphate concentrations in a paprika nutrient solution. As a conventional multivariate analysis approach using spectral data, partial least squares regression (PLSR) and principal components regression (PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…The first hidden layer used 45 nodes and the hyperbolic tangent (Tanh) activation, while the second hidden layer used 30 nodes and the rectified linear unit (ReLU) activation function ( Table 2). In the previous study [20], the results were verified through various combinations of active functions in the hidden nodes and parameter values, but no significant correlation was found. For training, the Levenberg-Marquardt algorithm was used, a gradient descent method for avoiding local minima and overfitting [20] of the 73,440 samples used for model development; training used 70%, validation 15%, and testing 15%.…”
Section: Neural Network Based Temperature Prediction Modelmentioning
confidence: 84%
See 1 more Smart Citation
“…The first hidden layer used 45 nodes and the hyperbolic tangent (Tanh) activation, while the second hidden layer used 30 nodes and the rectified linear unit (ReLU) activation function ( Table 2). In the previous study [20], the results were verified through various combinations of active functions in the hidden nodes and parameter values, but no significant correlation was found. For training, the Levenberg-Marquardt algorithm was used, a gradient descent method for avoiding local minima and overfitting [20] of the 73,440 samples used for model development; training used 70%, validation 15%, and testing 15%.…”
Section: Neural Network Based Temperature Prediction Modelmentioning
confidence: 84%
“…Models based on neural networks are suitable for both linear and nonlinear modeling and have been applied to greenhouse environment modeling and control logic [18][19][20]. Many studies have reported reliable results in environmental prediction modeling using artificial neural networks [18,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fusion technique has been applied to detect phosphate in hydroponic solutions. For example, Jung et al [35] used two types of sensors, i.e. NIR spectroscopy and cobalt electrode, to develop fusion for detecting PO 4 ion concentration in a paprika nutrient solution.…”
Section: Introductionmentioning
confidence: 99%
“…Though many approaches based on unique or associative fusion techniques have been used, the cobalt electrode has not been deployed yet in practical applications. This is because of some weaknesses such as it needs frequently abrading and electrode surface treating constantly to ensure induce oxidation reaction, which affects changes in the electrode signal band [35], [36]. Moreover, MSAM is considered to be the most suitable method for compensating the shortcomings of ISEs sensing systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of technical strategies has radically resolved the drawbacks of ISEs. Other investigations focused on predicting the ions that are not available through an ion-selective electrode (as such , , and Mg) were examined by fusing the datasets acquired from an array of available ISEs [ 20 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%